Organizational embeddedness and its effect on performance: an exploratory analysis for Malaysian business managers - Lokhman Hakim Osman (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
In advancing the Malaysian industrial and business cause Malaysian business managers may have to reflect properly on the ‘myth of downsizing’ in inter-organization context. Firms’ network structural positions exert different effects upon the firms’ level of relational capital outcomes in an upstream supply network. Previous researches had largely focused on the context of decentralized network structure. However, the supply network is a centralized network because of the existence of the focal firm the existence of which may influence the impact of relational capital outcomes. Hence, the objective of this study was to determine the type of network structural positions required to obtain reasonable relational capital outcome in upstream supply network through an exploratory analysis of a small material-intensive maritime industry. The study found that network structural positions, i.e. degree centrality, did contribute to firms’ level of relational capital trust. In conclusion, firms embedded in upstream supply network benefit differently in terms of relational capital through different degrees of embeddedness. Firms’ resources should be re-aligned to match the benefits of different network structural positions.